DEVELOPMENT TRENDS FOR ADULT EDUCATION AT THE BEGINNING OF THE XXI CENTURY: THE EXPERIENCE OF THE SLOVAK REPUBLIC - Samoilenko, Oksana (Mountain School of Ukrainian Carpaty, 2019)
The modern world postulates the tendency towards continuity in adult education, life expectancy. The question of adult education in time in the educational policy of the countries of the European Commonwealth: it acts as a factor in increasing the bone of life of citizens. Ukraine, with its aspirations to become a full member of the European Union, needs to study the experience of European countries in adult education in order to extrapolate it. In this context, the Slovak Republic can serve as a benchmark for introducing reforms into the domestic adult education field. The purpose of the article is to analyze the trends of adult education at the beginning of the XXI century in the Slovak Republic against the backdrop of European experience. Methods of research: on the basis of analysis and systematization of statistical information, normative legal documents, theoretical developments of Slovak scholars, a generalization of trends in the development of adult education in the Slovak Republic at the beginning of the 21st century. Identified during the study of trends in the development of adult education in the early 21st century show the public demand in adapting the existing educational content to the modern challenges of the present. The experience of the Slovak Republic confirms the effectiveness of the Eurointegration orientation of adult education development in the policy of increasing the competitiveness of a specialist in the labor market.